PENGARUH WAKTU PENANGKAPAN PADA SIANG DAN MALAM HARI MENGGUNAKAN ALAT TANGKAP MINI PURSE SEINE TERHADAP HASIL TANGKAPAN IKAN YANG DI DARATKAN DI LINGKUNGAN PONDOK PRASI : The Influence Of Catching Times Day And Night Using The Mini Purse Seine Fishing Device On Fish Catches That Are Land In Pondok Prasi Environment - Danial, Wahyu; Kotta, Raismin; Budi Satriya, I Nyoman; Nano Septian, I Gede (Yayasan Al-Amin Qalbu, 2023)
The purpose of this study was to determine the number of catches obtained when caught during the day and caught at night, to determine the most effective composition of catches during the day and at night from the Mini Purse Seine Fishing Gear. This research was conducted in Pondok Prasi Environment, Ampenan District, Mataram City for 1 (month) starting from October 1 to November 1, 2013. The method used in this research is the Experimental Method, namely conducting experiments to see a result that leads to affirmation of the position cause and effect between the variables to be observed. Based on statistical analysis using the Ttest test at the 5% level (0.05) it can be seen that the total weight of the catch (kg) in treatment X1 (during the day) and treatment X2 (at night) showed a significant difference, where Thit (2, 93) > Ttab (2.048) this means fishing using a mini purse seine fishing gear which is operated during the day and at night gives different catches but has no effect on the type of fish caught